(untitled)
This study aims to test the influence of ( 1) organizational culture variables on teacher performance; (2) the variable organizational commitment to teacher performance; and (3) self- efficacy variable on teacher performance. This research deg using the positivistic quantitative method, the sample in this study 53 res